Sodium silicate promotes wound healing by inducing the deposition of suberin polyphenolic and lignin in potato tubers - Han, Ye; Yang, Ruirui; Wang, Qihui; Wang, Bin; Prusky, Dov (Frontiers in Plant Science, 2022)
Wound healing is a postharvest characteristic of potato tubers through accumulating suberin and lignin, which could reduce decay and water loss during storage. This study aimed to explore the impact and mechanisms of sodium silicate on wound healing of potatoes. After being wounded, ‘Atlantic’ potato tubers were treated with water or 50 mM sodium silicate. The results showed that sodium silicate treatment accelerated the formation of wound healing structures, and significantly reduced the weight loss and disease index of tubers. Furthermore, sodium silicate induced the genes expression and enzyme activity of phenylalanine ammonia lyase (PAL), 4-coumarate: coenzyme A ligase (4CL) and cinnamyl alcohol dehydrogenase (CAD) involved into the phenylpropane metabolism, enhancing the synthesis of the main precursors of suberin polyphenolic (SPP) and lignin, such as coniferyl alcohol, sinapyl alcohol and cinnamyl alcohol. Meanwhile, the gene expression of StPOD and StNOX were activated and the production of O2-, and H2O2 was promoted, which could be used for injury signal transmission and oxidative crosslinking of SPP monomers and lignin precursors. Besides, antimicrobial compounds, total phenolics, and flavonoids were also induced. We suggest that sodium silicate could promote wound healing by inducing the deposition of SPP, lignin, and antimicrobial compounds in potato tubers.